Developing Folklore-Based Teaching Materials to Foster ‎Local Wisdom in Junior Secondary Indonesian Language ‎Classes - Andriani, Liza; Andra, Vebbi (JPI: Jurnal Pustaka Indonesia, 2023)
The study aims to develop and validate folklore-based teaching materials that integrate local wisdom into Indonesian language instruction for junior secondary students. Employing a research and development (R&D) design with the ADDIE model (analysis, design, development, implementation, evaluation), the study engaged more than 50 seventh-grade students at MTs Al-Qur’an Harsallakum, Bengkulu, alongside expert validators in content, language, and media. Data were collected through expert judgment, student questionnaires, and classroom trials, and analyzed using descriptive statistics. The results indicate that expert validation scores ranged from 64% to 90.3%, placing the materials in the “very feasible” category, while student responses confirmed high levels of clarity, cultural relevance, and usability. These findings demonstrate that the developed module is pedagogically sound and practically applicable, effectively enhancing students’ ability to understand and write folklore texts. The study concludes that folklore-based materials not only support literacy learning but also foster cultural preservation, offering a contextually responsive resource for Indonesian language teaching in junior secondary schools.